Differences in biological maturation, anthropometry and physical performance between playing positions in youth team handball - Matthys, S. P. J.; Fransen, J.; Vaeyens, R.; Lenoir, M.; Philippaerts, R. (Journal of Sports Sciences, 2013)
It was the goal of this cross-sectional study to examine differences in maturity, anthropometry and physical performance between youth handball players across different playing positions (i.e. goalkeeper, back, pivot and wing). Multivariate analysis of covariance (MANCOVA), accounting for biological maturation, was used to assess positional differences in 472 male youth handball players from three age groups: U14, U15 and U16. Differences in age at peak height velocity were found in all age groups. Backs were significantly more mature than wings in U14 and U15 and than wings and pivots in U16. Furthermore, backs are overall taller, have a bigger arm span and perform best on tests for strength, agility and speed, especially in the U15 age group. Therefore, it can be concluded that youth players with the most advanced maturation status and the most favourable anthropometry and physical fitness scores, are consistently positioned in the back position. Players with a less advanced maturity status and an overall smaller stature are placed on the wing or pivot positions. In conclusion, it seems that anthropometrical and maturational characteristics are used by coaches to directly and/or indirectly select players for specific field positions. This strategy is risky since anthropometry and maturity status change over the years.